ADVANCED NATURAL REGENERATION OF NATIVE ARBOREAL SPECIES IN THE SUB-FOREST OF SETTLEMENTS OF EUCALYPTUS SALIGNA SMITH., IN THE REGION OF MATA SUL DE PERNAMBUCO - Alencar, Antonia Lidiane de (2011)
The capacity of natural regeneration of native species in situations of competition with forest plantation trees can be considered an important factor in maintaining diversity. Therefore, the present study evaluated the natural regeneration of native species in the sub-forest of a settlement of Eucalyptus saligna Smith., located on the Biological Reservation of Saltinho – PE. To estimate the natural regeneration of the arboreal species, three stands of Eucalyptus saligna Smith were selected. In each one of them, 10 sub-units of 1.0 x 50 m were implanted, one being on the edge of the stand and the others with a distance of 10 m one from another. The analyses were established based on the level of inclusion of the arboreal species in natural regeneration with circumference from stem to height of 30 cm from the soil - (CAB0.30m) ≤  15 cm, and the classes of heights were distributed as follows: Class 1- arboreal individuals with heights (H) 1.0 ≤ H  ≤ 2.0; Class 2- with heights (H), 2 < H  ≤ 3; and ; Class 3- with heights (H) >3.0 m. To evaluate the floristic diversity at the species level, the Shannon index was used (H´). In total, 302 live individuals were sampled, belonging to 23 botanical families, 31 genera and 39 species. Based upon the results, it is possible to conclude that the Eucalyptus saligna tree does not preclude the natural regeneration of native species in the stand understory, however the floristic structure of the community is also influenced by edaphic factors and vicinity of seed sources